Study of Linguistics and Educational Values Contained in Surah Al-Alaq verses 1-5: Kajian Ilmu Lingustik dan Nilai Pendidikan yang Terkandung dalam Surah Al-Alaq ayat 1-5 - Agung Setiyawan; Hilda Fauziyah (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2023)
Surah Al-Alaq is one of the surahs that refers to knowledge by ordering reading as the key to knowledge. This study aims to determine the interpretation of each verse in Surah Al-Alaq as explained above based on the results of research by each commentator. This article uses qualitative descriptive data analysis research to examine the hidden meanings hidden in Surah Al-Alaq verses 1–5 from a verbal and figurative perspective. According to the theory of language rules, the word